Eco-centric Narratives and the Deconstruction of Anthropocentrism in Richard Powers’ The Overstory - Kishor Dhungana (Journal of Development Review, 2025)
This paper examines Richard Powers’ The Overstory through the lens of eco-criticism, focusing on its eco-centric narrative structure and the deliberate deconstruction of anthropocentrism. The novel challenges human-dominated worldviews by presenting trees not as passive background elements but as sentient, interconnected beings with their own form of agency and voice. Powers reshapes narrative conventions by interweaving diverse human characters whose lives are irrevocably altered by their relationships with trees, thereby emphasizing ecological interdependence and the intrinsic value of non-human life. The text destabilizes the traditional hierarchy that places humans above nature, replacing it with a more holistic and egalitarian ecological perspective rooted in deep ecology. By granting narrative authority to trees and forests and foregrounding environmental activism, The Overstory advocates for a reimagined ethical framework in which nature is no longer a resource to be exploited but a living community to be respected. Through an eco-critical analysis, this paper explores how Powers’ work functions as both a literary and environmental call to action, urging readers to reconsider their relationship with the natural world in the face of ecological crisis.